Study of Driver Behaviour for Road Safety - Thakur, Vikas (My University, 2019)
Drivers accounted with more information than they process, they make the unusual judgment, ignore critical instructions or information, fail to monitor other traffic and drive too slowly or have excessive incidents of eyes off the road time. This behaviour leads our attention to safety. Different traffic condition affects the acceptance and processing of information related to the driving task, leading to serious repercussion. The present study consisting of vision screening, choice reaction test, simulator study and visual behaviour using an eye-tracking device. The study reveals that only 3 per cent of the drivers had correct vision acuity. The mean reaction time and mean motor time was increasing with the age group but statistically, there was no difference in the mean motor time. Only age 25-30 years and 36-40 years shows a significant difference in the mean reaction time. In stress tolerance test the median reaction time increase with the fast representation of the visual stimuli. In slow, medium and fast reaction phase the driver performance between different age groups changes but statistically no difference found. In the simulator study, it was found that the performance of highly trained professional drivers was better than the private car driving subjects. The visual behaviour study shows that with the age gazes of the subject’s increases and fixation duration, saccadic duration also increases. Similarly, this study reveals that when given the same driving situation the highly trained professional drivers had the same attention during the task. Another study conducted in real environmental conditions to evaluate the fixation and reaction gaze points near the speed hump with speed variation showed that all subjects are more likely to have more focus of fixation with speed of 25kmph- 30kmph at a distance of 40m-50m from the speed hump. The findings highlighted the horizontal search span of the subjects was wider and the fixation area scattered for 100m-80m, where more distractions were found on the road and the driver attention between 0-20m becomes double than the attention between 20-40m. The outcomes from the proposed work will help to screen out different driving related risk-taking factors that lead to the chances of getting involved in road accidents and thus provide a safe road to the users.
ME Thesis
Keywords: CHOICE REACTION TIME; GAZE PLOTS; HEAT MAPS